Bioprocess engineering principles - Doran, Pauline M.
This welcome new edition discusses bioprocess engineering from the perspective of biology students. It includes a great deal of new material and has been extensively revised and expanded. These updates strengthen the book and maintain its position as the book of choice for senior undergraduates and graduates seeking to move from biochemistry/microbiology/molecular biology to bioprocess engineering